International Human Rights Law and the Right to Privacy under Pakistan’s Prevention of Electronic Crimes Act, 2016 - Mariam Sherwani; Prof. Dr. Farkhanda Zia (Al-Qanṭara, 2023)
The Prevention of Electronic Crimes Act, 2016 of Pakistan is contemptuous in various aspects, particularly because it brings the right to privacy –which is a fundamental right of an individual endorsed by Public International Law and Human Rights Law –to a compromising position, therefore the law needs a careful assessment to bring it with conformity with international law and human rights law. The right to privacy is an important fundamental right enjoyed by individuals. Public International law contains provisions for the maintenance and protection of the right to privacy. Human rights laws have always emphasized the maintenance of the privacy of data and declared the privacy of an individual to be sanctified. There are, however, certain instances where the right to privacy seemingly comes into conflict with national security. This can be witnessed in countries that face poor law and order situations and to cope with the situation the countries are compelled to make some harsh laws. One such example is the Prevention of Electronic Crimes Act, 2016 is the law that has been made to curb the illegal activities taking place in the online world. In doing so, the law appears to be violating some aspects of the right to privacy. This paper attempts to make a balance between the right to privacy and national security and identify the inconsistencies of the law with human rights law and also suggest ways to remove the inconsistencies.